Two new species of Portanini (Hemiptera: Cicadellidae: Aphrodinae) from Southeastern Brazil - Felix, Márcio; Mejdalani, Gabriel (Zootaxa, 2016)
Two new species, Portanus restingalis and Paraportanus marica, are described and illustrated from Restinga de Maricá, a sandy coastal plain in Rio de Janeiro State, Southeastern Brazil. Comparative notes on the two new species are given. Portanus youngi and Paraportanus eburatus are newly recorded from Brazil and Guyana, respectively. A checklist of all known species of Portanini with their geographic distribution is provided.